Clustering, innovations and trust: the essentials of a clusters strategy for Scotland - Mike Danson; Geoff Whittam (European Regional Science Association (ERSA), 1998)
This paper explores the extent of networking within the Scottish economy and its significance for innovation in products, processes and policy formation and implementation. Whilst the development agency for Scotland, Scottish Enterprise, seeks to establish networking through its policy statements and objectives, it has had only limited success in achieving these aims. This is somewhat surprising given the strength of the corporate consensus approach to regional policy in Scotland, with many other areas adopting the innovative Scottish partnership model as the way to organise local and regional development strategies (Danson et al 1997). Furthermore, there are historical precedents which demonstrate the advantages which can arise from production within industrial districts in the Scottish context (Slaven 1975). But an examination of the approach adopted by Scottish Enterprise to develop networking relationships reveals that certain key aspects which are essential for the establishment of value-added-partnerships (Johnston and Lawrence 1988) are missing. Recent events surrounding the financial markets of the Far East, namely South Korea, Indonesia and Japan, and the consequent retrenchment in their overseas investment strategies, underline the fragility of an economy dependent on direct foreign investment. The Scottish economy, with over a quarter of manufacturing employment in overseas owned plants, is particularly susceptible to the outcome of such speculative attacks. Scottish Enterprise, through the inward investment agency - Locate in Scotland, have been actively encouraging foreign direct investment by East Asian and American corporations. However, input-output linkages between branch plants and the indigenous sector have tended to be underdeveloped, with much value added to the Scottish economy restricted to wage incomes in assembly plants. Scottish Enterprise has also argued that there is a lack of new firm formation within the Scottish economy and has sought to remedy this situation (Scottish Enterprise 1993). One of the issues which it has identified in the update of its business birth rate strategy is the unwillingness of potential entrepreneurs to become actual entrepreneurs (Scottish Enterprise 1996). A way forward on this issue would be the establishment of a supportive infrastructure, that is networks, thereby lessening the isolation and the suspected risk for the potential entrepreneur. Additionally, the creation of networks for established firms can lead to added value for the firms belonging to the network. The possibilities of networking for enterprises within the Scottish economy are not lost on Scottish Enterprise, but the initial initiatives have met with limited success. Within this paper, we examine the theoretical basis of networks and identify the crucial dimensions in promoting innovation. We then proceed to analyse the critical dimensions of networking within the Scottish context, highlighting the missing elements from the approach adopted by Scottish Enterprise. Whilst there are problems with the current policy delivery, there already exist clusters and geographical groupings of firms which, given the right policy approach, could result in the development of value-added-partnerships/industrial districts, leading to the establishment of a wider indigenous industrial base. We conclude by suggesting amendments to existing policy initiatives which hopefully would result in a more successful networking structure developing.
Keywords: 330